2020
DOI: 10.1002/tesj.571
|View full text |Cite
|
Sign up to set email alerts
|

Indonesian students’ strategies to cope with foreign language anxiety

Abstract: Previous research reports that foreign language anxiety (FLA) is one of the affective factors exerting influence on foreign language learning. Myriad studies have examined how foreign language learners cope with foreign language anxiety. However, few studies have addressed the particular moments when students feel the most anxious and how they cope with this anxiety. The present study aims to (1) identify specific moments when students feel the most anxious; (2) investigate their coping strategies; and (3) rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 40 publications
1
10
0
1
Order By: Relevance
“…Additionally, Dwi (very anxious) also stated that her shy personality was the reason she felt anxious. This is in line with Abdurahman & Rizqi (2020) which suggested that students that anxious about negative evaluation tend to mind the business that is not related to the task. Moreover, Rina (mildly anxious) stated that her anxiety in speaking was provoked by fear of being scolded.…”
Section: Fear Of Negative Evaluationsupporting
confidence: 89%
See 1 more Smart Citation
“…Additionally, Dwi (very anxious) also stated that her shy personality was the reason she felt anxious. This is in line with Abdurahman & Rizqi (2020) which suggested that students that anxious about negative evaluation tend to mind the business that is not related to the task. Moreover, Rina (mildly anxious) stated that her anxiety in speaking was provoked by fear of being scolded.…”
Section: Fear Of Negative Evaluationsupporting
confidence: 89%
“…Afterward, fear of negative evaluation is explained as students' fear of others' evaluation toward their performances. Anxious students tend to have attention divided if they exaggeratedly centered their concern on negative evaluation of others, "instead of receiving information, their attention is drained as they try to find a solution that reduces people's negative evaluations, which are unrelated to their language task" (Abdurahman & Rizqi, 2020). It happens as the result of dread of getting a low score on the task, as they consider that academic score will affect their future (Naudhani, Wu, & Naudhani, 2018).…”
Section: Factors Of Foreign Language Anxietymentioning
confidence: 99%
“…Speaking anxiety can be one factor that inhibits the improvement of the students' speaking skill. Many researchers had found that foreign language speaking anxiety can affect the speaking performance (Abdurahman & Rizqi, 2020;Arnold & Brown, 1999;Çağatay, 2015;Horwitz, Horwitz & Cope, 1986;Mahmoodzadeh, 2012;Tsiplakides & Keramida, 2009;Yalçın & İnceçay, 2014;Yang, 2012). Moreover, Abdurahman & Rizqi (2020) stated that foreign language speaking anxiety gives negative effect on speaking performance.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers had found that foreign language speaking anxiety can affect the speaking performance (Abdurahman & Rizqi, 2020;Arnold & Brown, 1999;Çağatay, 2015;Horwitz, Horwitz & Cope, 1986;Mahmoodzadeh, 2012;Tsiplakides & Keramida, 2009;Yalçın & İnceçay, 2014;Yang, 2012). Moreover, Abdurahman & Rizqi (2020) stated that foreign language speaking anxiety gives negative effect on speaking performance. Horwitz, Horwitz & Cope (1986) also believed that anxiety brings serious impediments to the second language fluency and performance.…”
Section: Introductionmentioning
confidence: 99%
“…Research related to foreign language anxiety among Indonesian learners of English and other foreign languages has gained some attention thus far (i.e. Abdurahman & Rizqi, 2020;Hidayati, Dewi, Nurhaedin, and Rosmala, 2020). The research on listening anxiety, however, is still limited (i.e.…”
Section: E-issn 2541-0075 13mentioning
confidence: 99%